Medición estadístico del ordenamiento profesoral (2020)
The Professorial Statute of the Universidad de los Andes features within its guidelines how professors are ranked within the Professorial Ordinance. The three categories defined by Universidad de los Andes are: Assistant Professor, Associate Professor and Main Professor. Each category is determined by the fulfillment and performance in three main responsibilities: Teaching Work, Research Work and Institutional Development Work. These areas are universally known as teaching, research and extension. The Vice-Rector for Research and Creation is interested in learning how these guidelines are being developed in order to rank teachers properly. The main objective of this thesis is to use statistical techniques to evaluate the execution of the guidelines established in the Teacher's Ranking. The use of statistical techniques is intended to carry out an objective analysis on the information collected. Due to the availability of information, the study was carried out with the information collected from the Faculty of Sciences and Faculty of Engineering. The two faculties are considered relevant in the number of professors and in the activities carried out by their teaching staff. In the fulfillment of the objective of the thesis, the differences between the categories of the ranking are studied, in the execution of the Teaching Work, Research Work and Institutional Development Work. A comparison is also made between the Faculty of Sciences and the Faculty of Engineering.